2015
DOI: 10.1016/j.jmmm.2015.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Improving the sensitivity of asymmetric magnetoimpedance in exchange biased NiFe/IrMn multilayers

Abstract: a b s t r a c tWe investigate the asymmetric magnetoimpedance effect in exchange biased NiFe/IrMn multilayers and explore the possibility of tailoring the linear region of the curves around zero magnetic field by playing with the thickness of the ferromagnetic layers, probe current frequency, and the orientation between external magnetic field and exchange bias field direction. We quantify the sensitivity by calculating the dZ dH / H 0 | | = in a wide range of frequencies. The highest sensitivity is observed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…This type of the AMI has been observed initially in field-annealed amorphous ribbons [6,7]. For film structures, the AMI has been studied extensively in the exchange bias multilayers [8,9]. It was found that the linear behavior of the MI response can be tuned by modifying the angle between the external field and exchange bias field or by changing the frequency.…”
Section: Introductionmentioning
confidence: 87%
“…This type of the AMI has been observed initially in field-annealed amorphous ribbons [6,7]. For film structures, the AMI has been studied extensively in the exchange bias multilayers [8,9]. It was found that the linear behavior of the MI response can be tuned by modifying the angle between the external field and exchange bias field or by changing the frequency.…”
Section: Introductionmentioning
confidence: 87%
“…single domain) and thus the EB is solely determined by the AF spin structure. Subsequently, this thickness dependence has been experimentally confirmed in many systems [22,23]. However, when considering incomplete domain walls in the FM layer Mejia-Lopez et al [24] analytically predicted a crossover from…”
Section: Introductionmentioning
confidence: 89%
“…Subsequently, GMI effect has also been found in amorphous ribbons [74,75] and multilayer films. [76,77] The origin of the GMI effect is normally explained by the skin effect of the conductor under high frequency. In ferromagnetic amorphous micro-fibers, domain wall movement is affected by the external magnetic field, and the skin depth is dependent on the circumferential permeability, which changes as the circular domain wall moves.…”
Section: Gmi Effect Of Multi-component Amorphous Microfibersmentioning
confidence: 99%